# Prove these two integrals are equal. [closed]

Prove that: $$\forall n,m \in \Bbb N:\int_0^1 x^m(1-x)^n \,dx=\int_0^1(1-x)^mx^n \,dx$$

I really have no idea.

## closed as off-topic by Jack D'Aurizio, Alec Teal, jameselmore, Micah, yoknapatawphaOct 23 '15 at 17:52

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – Jack D'Aurizio, Alec Teal, jameselmore, Micah, yoknapatawpha
If this question can be reworded to fit the rules in the help center, please edit the question.

• Slow day on the hot questions..... – Alec Teal Oct 23 '15 at 13:55

Setting $t=1-x\iff x=1-t$, we have $\mathrm d\mkern1mu x=-\mathrm d\mkern1mu t$, hence the change of variable formula yields: $$\int_0^1 x^m(1-x)^n \,\mathrm d\mkern1mu x=\int_1^0(1-t)^m t^n (-\mathrm d\mkern1mu t)=\int_0^1t^n(1-t)^m \,\mathrm d\mkern1mu t=\int_0^1 x^n(1-x)^m \,\mathrm d\mkern1mu x.$$
• I don't see your last step. Why $\int_0^1 t^n(1-t)^m dt=\int_0^1 x^n(1-x)^m dx$ ? – Kelan Oct 23 '15 at 11:56
• Because $t$ and $x$ are dummy variables. It is the same with \sum_{i=1}^5 (2i-1)=\sum_{k=1}^5 (2k-1): they're both equal to 25. In other words: theyre just place-holders. – Bernard Oct 23 '15 at 12:07
Hint: with $u = 1-x{{{{{}}}}}$.
• Can you tell me more? I tried to use $u=1-x,$ but I was failed. – Kelan Oct 23 '15 at 10:29